2021
DOI: 10.1063/5.0029729
|View full text |Cite
|
Sign up to set email alerts
|

Bubble dynamics and pressure field characteristics of underwater detonation gas jet generated by a detonation tube

Abstract: An underwater detonation tube (DT) experiment is carried out in a water tank to investigate the bubble dynamics and pressure field characteristics of an underwater detonation gas jet. In the experiment, a 0.78 liter DT filled with a 0.29 MPa methane–oxygen mixture (equivalent to 0.85 mg of TNT, trinitrotoluene) is detonated. By means of high-speed photography and pressure field measurements, the jet process is divided into four different stages. The evolution patterns and features of the four stages are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The flow rate and direction of the electrolyte affect the movement and detachment of bubbles in the electrolyte. Higher flow rates promote bubble detachment, while lower flow rates may lead to bubble retention and aggregation [76,77]. In summary, bubble detachment is affected by a variety of factors, including electrode surface properties, electrolyte concentration, current density, bubble size and morphology, and flow conditions.…”
Section: Factors Influencing Bubble Detachmentmentioning
confidence: 99%
“…The flow rate and direction of the electrolyte affect the movement and detachment of bubbles in the electrolyte. Higher flow rates promote bubble detachment, while lower flow rates may lead to bubble retention and aggregation [76,77]. In summary, bubble detachment is affected by a variety of factors, including electrode surface properties, electrolyte concentration, current density, bubble size and morphology, and flow conditions.…”
Section: Factors Influencing Bubble Detachmentmentioning
confidence: 99%
“…Thereafter, a larger bubble with a diameter of d ≈3.5 mm exploded with a time delay (frame 6), despite it being subjected to shock compression earlier, being somewhat upstream with respect to the two bubbles that exploded earlier. Furthermore, this bubble expanded (frame 7), shrank again (frame 8) and expanded again (frames 9-11), taking the shape of a parachute (frames 12-14), and then broke up into small fragments (frames [15][16][17][18][19][20]. The processing of video records made it possible to gain information on the shockinduced motion of individual bubbles behind the traveling SW.…”
Section: Single Shock Wave Propagation In Bubbly Watermentioning
confidence: 99%
“…The diverging nozzle was shown to suppress water-gas mixing, increase the gas jet velocity, and enhance the bubble pulsation process. High-speed photography, digital particle image velocimetry, underwater pressure field measurements, and CFD calculations were used in [19,20] to study the two-phase flow nearby the open end of the detonation tube submerged in water. Stoichiometric explosive mixtures of methane, hydrogen, and acetylene with oxygen were detonated in the tube under the same fill conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the propulsion and specific impulse generated by the first detonation are significantly higher than the subsequent cyclic processes. To analyze the characteristics of the gas jet formed by a single detonation of the PDE, Liu [23] conducts an experimental and numerical simulation study of the single detonation of a PDE underwater, analyzing the expansion and shrinking process of the bubbles created by a gas jet via underwater detonation and the pressure characteristics of the flow field.…”
Section: Introductionmentioning
confidence: 99%